PROMOTING DEVELOPMENT AND ENVIRONMENTAL AWARENESS IN CHILDREN WITH DISABILITIES: AN APPROACH WITH ADAPTED PHYSICAL EDUCATION AND FUZZY LOGIC - Bezerra, Igor Felipe Oliveira; Campos, Paola Souto; Junior, Jorge de Almeida Brito (Seven Editora, 2024)
This study aimed to develop a fuzzy logic model to evaluate the impact of interventions in Adapted Physical Education and Environmental Education on the development of children with disabilities, covering physical, cognitive and environmental awareness aspects. The research sought to transcend conventional assessment approaches, implementing scenario simulations that mimic real conditions and incorporating variables such as motor coordination and understanding of environmental concepts. The interventions were evaluated using fuzzy rules, in order to measure the impacts on the various dimensions of development. Although the model has not been applied in a practical context with children, validation tests suggest its future applicability in practical studies. The results indicate that integrated and balanced interventions can effectively improve both physical and cognitive development. The use of fuzzy logic proved to be a robust tool for the detailed evaluation of progress, indicating that the developed model can contribute significantly to inclusive pedagogical practices and guide educational policies aimed at the needs of children with disabilities, reinforcing the importance of sustainability in environmental education. DOI:https://doi.org/10.56238/sevened2024.037-097